Pantoprazole-induced Stevens-Johnson Syndrome: A Case-report - Daldoul, Mouna; Charfi, Ons; Bouattour, Emna; Hammami-Ghorbe, Houda; Zaiem, Ahmed; Fenniche, Samy; Lakhoua, Ghozlane; El Aidli, Sihem (Current Drug Safety, 2024)
Introduction: Pantoprazole is a proton pump inhibitor mainly used to treat conditions causing excess stomach acid. Stevens-Johnson syndrome (SJS) is a rare bullous disease. The main etiologic factors are drugs, especially antibiotics, anticonvulsants, oxicam and allopurinol. Proton pump inhibitors have been rarely reported as a causative agent in SJS, and only sporadic cases secondary to pantoprazole have just been mentioned in the literature. Case Report: A 49-year-old woman was referred to the dermatology department for a pruritic generalized eruption, associated with erosive cheilitis. The patient reported self-medication by pantoprazole for two weeks. Physical examination revealed target-like lesions with bullous center in some areas. A skin detachment on the left breast and the neck affecting 10% of the total body surface area was observed. Mucosal examination revealed erosive, painful cheilitis covered by large hemorrhagic crusts and erosions of the nasal cavity. The lesions cleared completely few days after pantoprazole withdrawal and local corticosteroids. Further investigations ruled out infectious etiologies. Conclusion: This case highlights the possible occurrence of hypersensitivity reactions due to the use of a PPI, which is a widely used medication and a generally well-tolerated drug.
Keywords: adverse drug reaction